Understanding Plant Growth and Development in Preschool Children - Stepić, Gordana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
From early childhood, children build their understanding of scientific concepts through interactions with the world around them. Drawing emerges as a valuable methodology for gaining insight into children’s thoughts and ideas regarding different aspects of their environment. The aim of this study is to observe and analyze preschool children’s explanations of plant growth and development. The research is descriptive in nature, with a sample of sixty children aged 5.5 to 6.5 years. Data were collected using children’s drawings and an interview guide, and processed through content analysis. The findings indicate that preschool children’s understanding of the plant world begins during this period and is directly related to their firsthand experiences with plants at home and/or in kindergarten. Children employ a wide range of pictorial elements to represent plant growth and development and elaborate on their understanding through explanations of their drawings. These explanations are predominantly naturalistic and most often include factors such as the sun, water, and soil. The results suggest that preschool children are capable of constructing appropriate explanatory models, and further, that that the development of understanding and explanation—as integral elements of the scientific process—can and should be fostered through suitable strategies implemented by preschool educators.